Investigating the Use of Crystal Plasticity Finite Element (CPFE) Modeling to Determine Ballistic Performance of Novel Titanium Alloys - JONATHAN GORDON (2018)
The demand for lightweight and strong alloys in the aviation industry, such as titanium 6Al-4V, has grown with the increase in air travel. The fan blades on aero engines which are usually made from titanium 6Al-4V are susceptible to high strain rate deformation due to bird strike or other events associated with engine failure. The desire to optimise titanium alloys has lead to the desire for greater understanding of titanium deformation mechanics. In this research a hyperelastic-viscoplastic single-crystal rate-dependent material model is proposed. This model allows for the slip families of crystals to have their own unique material properties assigned to them. The crystallographic orientation is governed through the use of Euler angles. These Euler angles define the initial slip system configuration within the crystal. A method for generating computational microstructures known as representative volume elements for titanium 6Al-4V is detailed. The generated microstructures are compared to EBSD data and the correct volume fraction of beta phase is obtained. The average alpha grain size is also well matched but the beta grains are larger than found in the EBSD data set. The constructed microstructure is then meshed with brick elements and the model is used to simulate its response to macro and micro scale loadings. The model captures the general trends but does not give an exact match to the experimental data.